Atypical presentation of Charcot-Marie-Tooth disease type 2Q by mutations on DHTKD1 and NTRK2 genes - Dulce M. Castro-Coyotl; Israel E. Crisanto-López; Rosa M. Hernández-Camacho; María P. Saldaña-Guerrero (Permanyer, 2021)
Background: Charcot-Marie-Tooth disease type 2Q (CMT2Q) is a rare disorder (< 1/1,000,000 individuals worldwide) linked to chromosome 10p14 in the DHTKD1 gene. This phenotype is characterized by an adolescent or adulthood-onset, slowly progressive distal muscle weakness and symmetrical atrophy associated with reduced or absent deep tendon reflexes. Currently, only two familiar cases from China have been reported: one familiar case of eight individuals affected by isolated DHTKD1 gene mutation and one familiar case of two individuals affected by DHTKD1 gene mutation and GJB1 gene mutation. Case report: We present the case of a 10-year-old male patient with obesity, frequent falls, swollen legs and thighs, and pain in the lower and upper limbs. We performed the clinical evaluation and a clinical targeted exome test, which reported mutations on DHTKD1 y NTRK2 genes. Conclusions: Due to scientific and technological advances, genetic dysfunctions that can cause different diseases have been identified with greater sensitivity. Globally, this is the eleventh case reported of DHTKD1 gene mutation linked to CMT2Q. Moreover, this is the first case related to NTRK2 gene mutation (linked to obesity, hyperphagia, and delayed development). The patient showed an atypical CMT2Q phenotype additional to obesity. Therefore, we propose to study metabolic disorders linked to hereditary peripheral neuropathies.